Identification Of Sediment Thickness Using The Geomagnet Method in Beleka and Dasan Tapen Villages, Gerung District, West Lombok Regency - Izza Aulia Putri; Suhayat Minardi; Syamsuddin Syamsuddin (Kappa Journal, 2026)
Gerung is one of the sub-districts in West Lombok Regency. Based on data from BNPB the Gerung sub-district area is an area that is vulnerable to the natural phenomenon of earthquakes, because the soil in this area has a softer texture so that when vibrations occur, the vibrations will be stronger. Geologically, this alluvium formation is very vulnerable to the natural phenomenon of earthquakes because it is related to the thickness of the sediment. This research aims to determine the thickness of sedimentary rocks in the Gerung District. One of the Geophysical Methods used in this research is the Geomagnetic Method. Based on the 2-Dimensional modeling of the AA' - FF' Incision, it consists of five rock layers, namely the first layer includes Silt Rock, the second layer includes Sand Rock, the third layer includes Clay, the fourth layer includes Breccia Rock and the fifth layer includes Lava Rock. The composition of the five rock layers, layers including sedimentary rock is found in the first layer to the fourth layer. The results of the research for sediment thickness from the six incisions ranged from 405 m – 485 m. Based on the results of this research, it can be concluded that Beleka Village and Dasan Tapen Village it is composed of five rock layers with a dominant sediment thickness of 485 m, namely at the AA' incision in the western part of Beleka Village